Burn Patients in an Apex Institute: A Hospital Based Study from Maharashtra, India - Yerpude , Pravin N.; Jogdand , Keerti S. (Research Highlights in Disease and Health Research Vol. 1, 2023)
This short descriptive observational study had been undertaken to find out the material and social causes of burn and to assess the demographic and clinical profile and treatment outcome of burn patients in the KEM hospital, Mumbai, India. Burn injuries occur universally and have adversely affected mankind since antiquity till the present day. In all societies burns constitute a serious medical and psychological problem. Burn injuries constitute a major public health problem. A hospital-based descriptive observational study was conducted among 278 burn patients admitted in the KEM hospital, Mumbai in 2017 to assess the demographic and clinical profile of burn patients and to study the medico legal and social causes. Majority of patients were females (56.12%), literates (73.74%), in the age group of 21-40 years (49.64%). Occupation-wise housewives were 38.85% followed by unskilled worker (18.72%).Majority of the cases (55.04%) were accidental whereas suicidal and homicidal cases were 20.50% and 24.46% respectively. According to the size 25.3% patients had 20% -39% of body surface burns and 21.7% had 80% or more burns. 53% of the cases were given blood transfusion and 22.12% died in the study period. By educating people about safety precautions, enacting good health and safety laws, designing proper appliances, treating burn cases promptly, and using the right referral services, it is possible to significantly reduce mortality, morbidity, and disability due to burn injuries.